2020
DOI: 10.1038/s41366-019-0515-9
|View full text |Cite
|
Sign up to set email alerts
|

Commensal Hafnia alvei strain reduces food intake and fat mass in obese mice—a new potential probiotic for appetite and body weight management

Abstract: Background/objectives Based on the recent identification of E.coli heat shock protein ClpB as a mimetic of the anorexigenic α-melanocyte stimulating hormone (α-MSH), the objective of this study was to preclinically validate Hafnia alvei, a ClpBproducing commensal bacterium as a potential probiotic for appetite and body weight management in overweight and obesity. Methods The involvement of enterobacterial ClpB in the putative anti-obesity effects was studied using ClpB-deficient E.coli. A food-grade H. alvei H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
81
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(91 citation statements)
references
References 38 publications
4
81
0
1
Order By: Relevance
“…The lack of leptin in ob/ob mice results in strong hyperphagia underlying development of obesity even on a standard diet [13]. On the other hand, WT mice fed HFD develop diet-induced obesity (DIO), which is typically accompanied by a decreased total (but not caloric) food intake, a phenomenon which was also observed in our previous study, representing an obstacle for the evaluation of a potential H. alvei anorexigenic effect in palatable HFD [11]. An animal model of obesity based on HFD-fed ob/ob mice may represent a good alternative most closely reflecting hyperphagia and diet-induced obesity in humans.…”
supporting
confidence: 61%
See 2 more Smart Citations
“…The lack of leptin in ob/ob mice results in strong hyperphagia underlying development of obesity even on a standard diet [13]. On the other hand, WT mice fed HFD develop diet-induced obesity (DIO), which is typically accompanied by a decreased total (but not caloric) food intake, a phenomenon which was also observed in our previous study, representing an obstacle for the evaluation of a potential H. alvei anorexigenic effect in palatable HFD [11]. An animal model of obesity based on HFD-fed ob/ob mice may represent a good alternative most closely reflecting hyperphagia and diet-induced obesity in humans.…”
supporting
confidence: 61%
“…Indeed, traditional probiotic bacteria belonging to the genera of Lactobacillus, Bifidobacterium, and Enterococcus, alone or in various combinations, have been tested in humans, resulting typically in minor health-positive effects, without significant changes in food intake and body weight [6][7][8][9]. Nevertheless, existence of the functional link between gut microbiota and host regulation of appetite and energy metabolism indicates that some gut commensal bacteria can be potentially identified and developed as new-generation anti-obesity probiotics based on the understanding of their mechanisms of action [10].We have recently demonstrated that a Hafnia alvei (H. alvei) HA4597™ strain of commensal bacteria of the Hafniaceae family (formerly Enterobacteriaceae) belonging to the order of Enterobacteriales displays anti-obesity properties in two animal models of obesity, standard-diet-fed leptin-deficient ob/ob and high-fat-diet (HFD)-fed wild-type (WT) mice [11]. The choice of H. alvei as a potential anti-obesity probiotic was based on its production of the caseinolytic protease B (ClpB) protein, which was previously identified as a conformational mimetic of α-melanocyte-stimulating hormone (α-MSH), a key anorexigenic peptide involved in the regulation of appetite [11,12].In the present study, we aimed to test the anti-obesity efficacy of the H. alvei HA4597™, in a mouse model of obesity characterized by both hyperphagia and HFD-induced adiposity.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Some of the reported beneficial effects of probiotics in human health include anticancer [99][100][101][102][103][104][105][106][107][108][109][110][111], anti-allergic [112,113], anti-diabetic [114][115][116], anti-obesity [117][118][119][120], anti-pathogenic [121,122], immunomodulatory [123], and anti-inflammatory [124][125][126][127] activities [128], as reported in Table 1.…”
Section: Health Promoting Effect Of Prebiotics Probiotics and Synbimentioning
confidence: 99%
“…The body weight and abdominal fat content were decreased in mouse models fed a modified diet through the administration of L. plantarum LMT1-48 at a density of 10 6 CFU/mL [117] Hafnia alvei Anti-obesity effect Fat mass, food intake, and body weights were reduced in the mouse model of obesity and hyperphagia [118]…”
Section: Health Promoting Effect Of Prebiotics Probiotics and Synbimentioning
confidence: 99%